Pembelajaran Kebugaran Jasmani Melalui Permainan BOI (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve the learning outcomes of physical fitness through modification boi game in Class II MI Assalafiyah Kemanggungan Tarub District of Tegal in the academic year 2013/2014. Methods that researchers use in the form of classroom action research (PTK) carried out by the research subject is class II MI Assalafiyah Kemanggungan totaling 26 students consisting of 10 male students and 16 female students. Based on the results of the study showed an increase in learning outcomes, with KKM 75 in cycle 1 percentage success of 76.92%, of the 26 students, there are 6 students who have not completed, while in the second cycle of the passing percentage increased to 96.15%, from 6 children incomplete be one child who has not been completed. From the research results with PTK method can be concluded that physical fitness through modification learning BOI games can improve student learning outcomes.